Implementation of a Post-Secondary Inclusive Recreation Program - Brown, Chris; Johnson, John David; Elsawy, Ibrahim Z. (Journal of the American Academy of Special Education Professionals, 2017)
As individuals with intellectual or developmental disabilities become increasingly involved in post-secondary educational opportunities, it becomes the responsibility of the institution to provide inclusive recreation opportunities. This manuscript incorporates Sugermans’ (2001) Model of Inclusive Facilitation into an inclusive recreation program for students with disabilities within a post-secondary based recreation program. The program model presented demonstrates a deliberate attempt to address and implement inclusive recreation opportunities for post-secondary students with disabilities outside of the traditional intramural/campus recreation model. The goal of the program is to enable post-secondary institutions to be comfortable and competent in creating inclusive recreation programs for students with disabilities by developing the ability to focus on participants’ abilities.